Reflection coefficient estimation by pseudospectrum matching - Marković, D.; Hofmann, Christian; Antonacci, F.; Kowalczyk, Konrad; Sarti, A.; Kellermann, Walter (International Workshop on Acoustic Signal Enhancement (IWAENC), 2012)
This paper presents a novel model-based method for in-situ estimation of sound reflection coefficients in acoustic enclosures. The method uses a modeling engine for simulation of acoustic propagation and generation of the spatial pseudospectrum using a beamforming technique. The simulated pseudospectrum is matched with the measured pseudospectrum acquired by a real beamforming microphone array in order to estimate reflection coefficients of the walls of the acoustic enclosure. Experimental results confirm that the proposed method allows for an accurate estimation of the reflection coefficients, especially for reflective walls, typical of everyday environment
Keywords: Beamforming; Microphone array; Reflection coefficient estimation